Excited delirium: race, police violence, and the invention of a disease - Beliso-De Jesús, Aisha M. (Duke University Press, 2024)
Aisha M. Beliso-De Jesús examines the emergence of excited delirium syndrome in the 1980s, a fabricated medical diagnosis used to justify and erase police violence against Black and Brown communities in the United States